Evaluation of AlphaFold2 structures as docking targets. (22nd December 2022) - Holcomb, Matthew; Chang, Ya‐Ting; Goodsell, David S.; Forli, Stefano
Abstract: AlphaFold2 is a promising new tool for researchers to predict protein structures and generate high‐quality models, with low backbone and global root‐mean‐square deviation (RMSD) when compared with experimental structures. However, it is unclear if the structures predicted by AlphaFold2 will be valuable targets of docking. To address this question, we redocked ligands in the PDBbind datasets against the experimental co‐crystallized receptor structures and against the AlphaFold2 structures using AutoDock‐GPU. We find that the quality measure provided during structure prediction is not a good predictor of docking performance, despite accurately reflecting the quality of the alpha carbon alignment with experimental structures. Removing low‐confidence regions of the predicted structure and making side chains flexible improves the docking outcomes. Overall, despite high‐quality prediction of backbone conformation, fine structural details limit the naive application of AlphaFold2 models as docking targets.